The use of vacuum fine needle aspiration biopsy of small formations in the diagnosis of thyroid cancer - A. O. Tagil; A. V. Borsukov (Опухоли головы и шеи)
Introduction. Diagnosis and treatment of lesional pathology of the thyroid are important problems in Russia and worldwide. Currently, fine-needle aspiration (FNA) is the main technique of differential diagnosis of benign and malignant tumors of the thyroid. In 2023, clinical guidelines of the European Thyroid Association (ETA) on thyroid lesion treatment were published noting possible minimally invasive treatment of benign and malignant tumors of the thyroid requiring repeat cytologic verification. Despite the proven effectiveness of FNA, its informativity and specificity vary between 60 and 100 %. Additionally, this method is associated with high risk of false negative and false positive results. Therefore, there is a need to improve FNA and minimize its disadvantages.Aim. To evaluate the capabilities of vacuum FNA of small lesions using multiparameter ultrasound in diagnosis of thyroid cancer.Materials and methods. At the scientific and practical problem laboratory Diagnostic Studies and Minimally Invasive Technologies of the Smolensk State Medical University, a device for vacuum FNA was developed. Between 2023 and 2024, patients with thyroid lesions of size <10 mm underwent 25 vacuum FNAs. Correlation analysis with 51 FNAs performed between 2020 and 2023 was performed.Results. A decrease in the number of nondiagnostic (category I per the Bethesda system, 2017) and undetermined (category III per the Bethesda system, 2017) results was observed. Comparison of preoperative cytologic conclusions (category V per the Bethesda system, 2017) with the results of postoperative histological examination in patients of the control group showed benign lesions in 2 (50 %) cases which correspond to false negative results. Vacuum FNA did not show this discrepancy. These results demonstrate a decrease in the probability of false negative results and effectiveness of vacuum FNA.Conclusion. Use of vacuum FNA expedites ultrasound-guided biopsy for small thyroid lesions. Due to high negative pressure (up to –0.8 bar), single-step retrieval of cytologic material is performed which leads to a decrease in the number of nondiagnostic and undetermined cytologic conclusions by 11.7 and 1.9 %, respectively.